ANALYSIS OF DETERMINING PRIORITY OF ROAD HANDLING PROGRAM IN THE REGION OF KEDIRI ROAD AND BRIDGE MANAGEMENT DEPARTMENT OF HIGHWAYS EAST JAVA PROVINCE USING MULTI CRITERIA ANALYSIS (MCA) METHOD - Haniffan Daruquthni Baihaqi; Catur Arif Prastyanto (Institut Teknologi Sepuluh Nopember, 2023)
Steady road conditions determine the smooth running of land transportation to support economic activity. To achieve steady road conditions requires a good road management program. The government, through the agencies appointed as road administrators, needs funds to maintain the stability of the road itself. The process of budgeting funds for the implementation of the road through a process of proposals, discussions and determination of the budget. Determining the priority of the proposal requires a long discussion. The Provincial Government of East Java through the Department of Public Works of Highways has an important role in the process of handling provincial roads. Budget limitations, both Regular APBD funds and special allocation funds and other funds, create a distinct challenge for road administrators in determining an effective and optimal road management program. Based on previous research studies, priority determination of road handling can be carried out using Multi Criteria Analysis (MCA). Priority determination criteria used in this study are technical criteria which include: existing traffic conditions, road stability conditions, degree of saturation, travel speed, and travel time; financial and economic criteria which include: BOK, Time Value, BCR, and NPV. In this study it will be seen based on the results of prioritized maintenance handling found at Link 176 Kediri - Blitar City Boundary for LHR technical criteria has a difference in value of 3,190 cur/hour, with an average road condition of 27.12%, difference in degree of saturation of 0.346, the difference in travel speed is 3.409 km/hour, the difference in travel time is 3.661 minutes and for economic criteria BOK has a difference in value of Rp. 8,662,656,168, the difference in the BCR value is 0.60 and the difference in the NPV value is -Rp. 8,382,143,904.